Challenges in achieving partial nitrification: Simultaneous nitrification-denitrification as the dominant pathway in municipal wastewater treatment - Takeda, Paula Yumi; Tavares Paula, Carolina; Braz Carneiro, Rodrigo; do Vale Borges, André; Cardoso Grangeiro, Luana [UNESP]; Rissato Zamariolli Damianovic, Márcia Helena (Elsevier, 2025)
Partial nitrification (PN) is pivotal for energy-efficient nitrogen removal in wastewater treatment, yet challenges persist in stabilizing PN, particularly in mainstream municipal wastewater treatment. This study explores five operational strategies to optimize PN, encompassing varying dissolved oxygen (DO) concentrations, intermittent aeration, pH adjustment, hydraulic retention time (HRT) regulation, and nitrifying sludge treatment with free nitrous acid, alongside implementing short sludge retention time (SRT). Bench-scale reactor applying plug and continuous stirred flow regimes were employed, alongside a comprehensive analysis of microbial community dynamics. Despite efforts to suppress nitrite-oxidizing bacteria (NOB) and retain ammonium-oxidizing bacteria (AOB), stable PN was not achieved. Nevertheless, the simultaneous nitrification-denitrification (SND) process was identified as the primary pathway in this study. Nitrite accumulation ratio (NAR) ranged from 0 % to 97 % throughout the experimental period. The microbial community analysis revealed shifts in abundance and diversity, with heterotrophic denitrifiers dominating under low DO (0.1–0.2 mg L−1) and alkaline condition (pH = 8.6 ± 0.1). Notably, Ottowia (18.9 %) and Limnobacter (16.0 %) genera exhibited increased abundance, which corroborates the hypothesis of the SND pathway occurrence. This occurrence resulted in nitrogen removal efficiency up to 43.2 ± 5.9 %. Moreover, Nitrospira prevalence underscored NOB persistence despite operational strategies. While the study provides insights into PN and SND processes dynamics and microbial responses, further optimization is essential for stable PN in mainstream wastewater treatment.
Keywords: Anaerobically pre-treated wastewater; Free nitrous acid treatment; Intermittent aeration; Low dissolved oxygen; Municipal wastewater; Nitrite-oxidizing bacteria